A study of the microwave actuation of a liquid crystalline elastomer. Issue 31 (20th July 2020) - Wang, Xiuxiu; Wang, Yuchang; Wang, Xixi; Niu, Hongyan; Ridi, Buyinga; Shu, Jincheng; Fang, Xiaoyong; Li, Chensha; Wang, Binsong; Gao, Yachen; Sun, Liguo; Cao, Maosheng
Abstract : We developed microwave actuation of LCEs. The microwave can penetrate opaque barriers and multiple samples to effectively actuate the LCEs. A LCE-based microwave detector was fabricated and monitored the microwave irradiation with well sensitivity. Abstract : We present a method for actuating LCE materials by microwave radiation. The microwave actuation performance of a polysiloxane-based nematic liquid crystalline elastomer (LCE) was investigated. The microwave–material interaction caused a dipolar loss, which created a heating effect to trigger the nematic–isotropic transition of the LCE matrix, thus leading to the deformation actuation of the LCE material. This energy conversion from radiant energy to thermal energy provided a contactless pathway to actuate the LCE material without the aid of other components acting as energy converters. The LCE demonstrated rapid maximum contraction upon microwave irradiation, and this microwave-stimulated response was fully reversible when the microwave irradiation was switched off. More importantly, the microwave actuation exhibited superiority relative to photo-actuation, which is the usual method of contactless actuation. The microwaves can penetrate the opaque thick barriers to effectively actuate the LCE due to their strong penetrability; they can also penetrate multiple LCE samples and actuate them almost simultaneously. By taking advantage of the salient features of microwave actuation, a microwave detector system, implementing the LCE as an actuator material, was fabricated. This demonstrated the performance of monitoring microwave irradiation intensities with good sensitivity and convenient manipulation.